2010
DOI: 10.1016/j.ydbio.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

BDNF is essentially required for the early postnatal survival of nociceptors

Abstract: Neurotrophins promote the survival of specific types of neurons during development and ensure proper maintenance and function of mature responsive neurons. Significant effects of BDNF (Brain-Derived Neurotrophic Factor) on pain physiology have been reported but the contribution of this neurotrophin to the development of nociceptors has not been investigated. We present evidence that BDNF is required for the survival of a significant fraction of peptidergic and non-peptidergic nociceptors in dorsal root ganglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Compelling evidence has demonstrated that the overexpression of BDNF is essential for development of neuropathic pain and inflammatory pain (Siuciak et al, 1994(Siuciak et al, , 1995Eaton et al, 1997;Thompson et al, 1999;Kerr et al, 1999;Mannion et al, 1999;Cejas et al, 2000;Deng et al, 2000;Ramer et al, 2000;Obata et al, 2003;Coull et al, 2005;Hayashida et al, 2008;Miletic and Miletic, 2008;Trang et al, 2009;Yang et al, 2009;Zhou et al, 2009;Geng et al, 2010;Valdes-Sanchez et al, 2010). We also show that i.t.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Compelling evidence has demonstrated that the overexpression of BDNF is essential for development of neuropathic pain and inflammatory pain (Siuciak et al, 1994(Siuciak et al, , 1995Eaton et al, 1997;Thompson et al, 1999;Kerr et al, 1999;Mannion et al, 1999;Cejas et al, 2000;Deng et al, 2000;Ramer et al, 2000;Obata et al, 2003;Coull et al, 2005;Hayashida et al, 2008;Miletic and Miletic, 2008;Trang et al, 2009;Yang et al, 2009;Zhou et al, 2009;Geng et al, 2010;Valdes-Sanchez et al, 2010). We also show that i.t.…”
Section: Discussionsupporting
confidence: 61%
“…As we know, in normal animals, BDNF is most prominent in terminals of laminae I-II of the spinal dorsal horn. It may be released from primary afferent terminals within the spinal cord after inflammation or nerve injury and regulate nociceptive transmission in the spinal dorsal horn (Cejas et al, 2000;Ramer et al, 2000;Obata et al, 2003;Valdes-Sanchez et al, 2010). In addition, in neuropathic pain, the increased BDNF in the spinal cord is expressed mainly in the activated microglia (Coull et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF regulates spinal central sensitization via releasing anterogradely to the superficial dorsal horn of the spinal cord where TrkB is expressed (Papadia and Hardingham, 2007; Zhou and Rush, 1996). Paracrine secretion of BDNF within the DRG has also been documented (Valdes-Sanchez et al, 2010). However, the signal transduction of BDNF within the DRG has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nociceptive sensory neuron loss is found to occur in BDNF-deficient mice during the postnatal period, suggesting that neurotrophins are important for developing neurons to cope with environmental stimuli (64). Neurotrophins act on their membrane receptors to trigger receptor endocytosis, and the function of endocytic receptors largely relies on their intracellular sorting, which can be degraded by the lysosomes, recycled to the plasma membrane, or transported to different cellular compartments to elicit distinct signaling and function.…”
Section: Discussionmentioning
confidence: 99%